Resource Allocation Techniques in Edge/Fog Computing - Majumder, Darpan; Kumar, S. Mohan; Ashoka, D. V.; Nargunam, A. Shajin (2021 International Conference on Advances in Electrical, Computing, Communication and Sustainable Technologies (ICAECT), 2021)
The advent of IOT has resulted in explosion of connected devices. These devices generally have limited computing capabilities and to overcome this there is a new distributed computing architecture in the form of edge computing. In this paradigm some part of the computation is performed at the edge of the network and the rest either in the end point nodes or the cloud depending on the task that needs to be completed. This method opens new challenges specially in the form of resource allocations in the edge computing framework. In this work we shall be looking into the major resource allocation paradigms present and new approaches to this problem